Subcommissural Organ-Spondin-Derived Peptide Restores Memory in a Mouse Model of Alzheimer’s Disease - Le Douce, Juliette; Delétage, Nathalie; Bourdès, Valérie; Lemarchant, Sighild; Godfrin, Yann (Frontiers in Neuroscience, 2021)
Alzheimer’s disease (AD) is a devastating neurodegenerative disease that affects millions of older people worldwide and is characterized by a progressive deterioration of cognitive functions, including learning and memory. There are currently very few approved treatments (i.e., acetylcholinesterase inhibitors such as donepezil), all of which are limited to the symptomatic control of AD and are associated with side effects that may result in discontinuation of treatment. Therefore, there is an urgent need to develop disease-modifying treatments to prevent AD-induced cognitive deficits. Subcommissural organ (SCO)-spondin is a brain-specific glycoprotein produced during embryogenesis and has a substantial impact on neuronal development. In the current study, we sought to evaluate the protective effects of the linear (NX210) and cyclized (NX210c) forms of a SCO-spondin-derived peptide on learning and memory in a mouse model of AD. Mice received an intracerebroventricular injection of Aβ25-35 oligomers and were subsequently treated with intraperitoneal injections of vehicle, NX210 or NX210c of different doses (ranging from 0.1 to 30 mg/kg) and therapy paradigms (early or late stand-alone treatments, combination with donepezil or second-line treatment). Cognitive function was evaluated using Y-Maze, step-through latency passive avoidance (STPA) and Morris water maze (MWM) tests for up to 4 months. Early-stage daily treatment with NX210 and NX210c decreased the levels of common pathological markers and features of AD, including Aβ1-42, phosphorylated-tau, inflammation, astrogliosis and lipid peroxidation. Meanwhile, use of these drugs increased the levels of synaptophysin and postsynaptic density protein 95. Regardless of the experimental paradigm used, NX210 and NX210c prevented Aβ25-35-induced decrease in spontaneous alternations (Y-Maze) and step-through latency into the dark compartment (STPA), and Aβ25-35-induced increase in time needed to locate the immersed platform during the learning phase and decrease in time spent in the target quadrant during the retention phase (MWM). Interestingly, this study provides the novel evidence that the native and oxidized cyclic forms of the SCO-spondin-derived peptide reduce pathological factors associated with AD and restore learning and memory at both early and late disease stages. Overall, this study sheds light on the therapeutic potential of this innovative disease-modifying peptide to restore memory function in patients with AD.